Assessment of IgG Antibodies Against HSV1, HSV2, CMV and EBV in Patients with Pemphigus Vulgaris versus Healthy People - Parichehr Ghalayani; Fateme Rashidi; Zahra Saberi (Tehran University of Medical Sciences, 2016)
Objectives: Regarding the implication of viruses particularly herpes in pemphigus vulgaris, we sought to assess and compare the level of immunoglobulin G (IgG) antibodies against herpes simplex virus types 1 and 2 (HSV1 and HSV2), cytomegalovirus (CMV) and Epstein-Barr virus (EBV) in patients with pemphigus vulgaris and healthy people.     Materials and Methods: In this cross-sectional study, 25 patients with pemphigus vulgaris and 27 healthy individuals comprised the experimental and control groups, respectively. Serum samples were taken from both groups; the levels of IgG antibodies against HSV1, HSV2, CMV and EBV were measured using ELISA.   Results: Immunoglobulin G titer was higher for all four viruses in the patient group in comparison to the control group. This difference was significant for anti-EBV (P= 0.005), anti-CMV (P=0.0001) and anti-HSV2 (P=0.001) but not significant for anti-HSV1 (P= 0.36). Conclusion: Viruses including EBV, CMV, and HSV2 probably play a role in the pathogenesis of pemphigus in addition to the effects of genetics, toxins and other predisposing factors. In this study, no statistically significant relationship was observed between HSV1 and pemphigus vulgaris, which was probably due to the high titer of anti-HSV1 IgG in healthy individuals in the community. More studies must be done in this regard.